2022
DOI: 10.48550/arxiv.2211.04711
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gravitational wave constraints on spatial covariant gravities

Abstract: The direct discovery of gravitational waves (GWs) from the coalescence of compact binary components by the LIGO/Virgo/KAGRA Collaboration provides an unprecedented opportunity for exploring the underlying theory of gravity that drives the coalescence process in the strong and highly-dynamical field regime of gravity. In this paper, we consider the observational effects of spatial covariant gravities on the propagation of GWs in the cosmological background and obtain the observational constraints on coupling co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…The case with β ν = 2 can arise from the spatial covariant gravities [55,91] and the Hořava-Lifshtz gravity with mixed derivative coupling [37]. This case corresponds to a specific…”
Section: β ν =mentioning
confidence: 99%
See 1 more Smart Citation
“…The case with β ν = 2 can arise from the spatial covariant gravities [55,91] and the Hořava-Lifshtz gravity with mixed derivative coupling [37]. This case corresponds to a specific…”
Section: β ν =mentioning
confidence: 99%
“…The case with β μ = 2 can arise from a large number of Lorentz-violating theories of gravity, including the chiral Weyl gravity [93], spatial covariant gravities [55,91], Hořava-Lifshitz gravity [32,33,35], diffeomorphism/Lorentz violating linear gravity in the standard model extension [45,46], consistent four-dimensional Einstein-Gauss-Bonnet gravity [61,94,95], Lorentz-violating Weyl gravity [96], etc. This case corresponds to a nonlinear dispersion relation of GWs.…”
Section: β μ =mentioning
confidence: 99%
“…A large class of SCG Lagrangians without any scalar degree of freedom has been investigated in [17,18] and applied in the study of cosmology and black holes [19][20][21][22]. 1 Additionally, constraints from gravitational waves on SCG have been explored in [28][29][30][31], from which one can see that SCG provides a broad framework to study various modified gravity theories in a unifying manner.…”
Section: Introductionmentioning
confidence: 99%
“…Other recent studies on parity violating gravities can be found in Refs. [22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%